(untitled) (Journal of Comparative & International Higher Education, 2022)
The notion of the “Entrepreneurial University” refers to a type of educational institution that enhances university-industry cooperation, applies innovative learning methods, and promotes multidisciplinary approaches. This article explores new challenges that Azerbaijani universities have faced as part of the Azerbaijani higher education transformation in the post-Soviet period. The research investigated the experiences of Western-style universities that have been building relationships with Western partners with substantial leadership experience in university innovation and, specifically, in establishing entrepreneurial universities. This paper argues that Azerbaijan’s transition to a knowledge economy will require a substantive transformation of the country’s higher education system and, as such, must develop the entrepreneurial university model that has been embraced as an effective response to the challenges of our time by some U.S. universities.